Respostas

2014-05-08T11:25:47-03:00
A (-3/4) + (-1/2) : (+1/4) =


     3               1        1              DIVISÃO conserve o  1º) e multiplica
-  ------- + (-   -------- :  --------) =    invertendo o 2º)
     4                2        4 



     3                1         4
-  -------- +  ( -   ----- X  -------) =
     4                2         1

     3                   4
-  -------     -      ----------- =   
     4                   2      mmc de 2: 4 = 4

 - 3          -          8              12
 ------------------------------ =   -  -------    =   - 3
             4                            4


b [(+2)-(-3/2) : (-3/2)].(-1/2)=

                 3          3           1
[(+2) -( -   ------ : - ------)] . (-  ----) =
                2          2            2  
              

                3         2               1     
[(+2) - ( -  ----  x - ---- )] .  ( -  -----) =
                2         3               2


                6            1
[(+2) - ( + ------ )] . (- ----) =    
                6       .     2  

                 1
[2 - 1]  . (- ----) =
                 2


1 x  (-1)          1
      ------ =  -  ------ =    - 1/2
        2            2




c [(+1/2).(-3/4)-(+1/2) : (-2/3)] : (-3/4) =




       1              3         1          2            3
[ (+ -----    x   - -----) - (+---)  : (- ---)] :  (- ------)=
        2             4          2         3           4


            3                    1          3            3
[( -   -----------------) - ( + ---- x -  ------)] :  (-  ----) =
            8                    2          2             4


            3                        3                    3
[( -    ---------- +           ------------ )] :       - -------
           8                         4                    4

        - 3          +              6                   3                                
  [-----------------------------------------] :      - ---------- 
                    8                                     4


                 3               3
            ----------- : -  ----------
                 8                4

      
         3              4              12           1
     --------   x   - ------- =   -   ------ = - --------- = -1/2
         8              3              24            2





d (-3).9+1,25)-(+1,2) : (-0,6)=  



(-3). 9 + 1,25 ) - (+1,2) : (-0,6) =



- 27 + 1,25        -    (- 2) =
    - 25,75   + 2 =   -  23,75